Prospects and Challenges Encountered by Varsity Student-Athletes: Perspectives from Wushu Varsity Athletes - Dawood, Muhammad; Ali, Asif; Ahmed, Fariq (Annals of Human and Social Sciences, 2023)
This study delves into the comprehensive examination of the unique challenges and growth potential among wushu players in Pakistan. The study engaged a diverse sample of 160 wushu players from ten different universities. This sample displayed a balanced gender distribution and an age range of 19 to 25 years. Data collection was accomplished through a 39-item Liker-type survey with a Cronbach’s alpha value 0.885. Data analysis primarily utilized simple descriptive statistics. The findings revealed noteworthy concerns among wushu players, primarily in the areas of nutritional support and fitness training, highlighting notable deficiencies. In contrast, wushu players also expressed a generalized satisfaction with the quality of facilities and equipment, coaching, financial incentives, administrative management and academic performance support within their respective universities. By proactively addressing the identified challenges and capitalizing on the strengths outlined in this study, the stakeholders might significantly enhance the overall experience and performance of wushu players.